Laparoscopic Surgery for Pheochromocytoma in Hemodialysis Patients - Shuichi Tatarano; Akihiko Mitsuke; Takashi Sakaguchi; Ryosuke Matsushita; Satoru Inoguchi; Hirofumi Yoshino; Hiroaki Nishimura; Yasutoshi Yamada; Hideki Enokida (International Journal of Nephrology)
Objectives. We analyzed the clinical outcomes of laparoscopic adrenalectomy for pheochromocytomas in hemodialysis compared with nonhemodialysis patients. Methods. Fifty-seven patients (7 hemodialysis and 50 nonhemodialysis) were included in the study. We analyzed the differences in clinical parameters and outcomes between the hemodialysis patient groups and nonhemodialysis patient groups as well as identified predictors for an intraoperative hypertensive spike. Results. The increasing intravascular volume before surgery in hemodialysis patients made perioperative hemodynamic management safer. No significant difference in clinical parameters between the two groups was observed except for the length of hospitalization that was significantly longer in the hemodialysis patients (9 vs. 6 days, P=0.005). An increase in systolic blood pressure at CO2 insufflation was an independent predictor of a hypertensive spike with a cutoff value of 22.5 mmHg (odds ratio 1.038, 95% confidence interval 1.012–1.078). Conclusion. Laparoscopic adrenalectomy for pheochromocytomas in hemodialysis was safe and feasible. An increase in systolic blood pressure at CO2 insufflation was a predictor of the intraoperative hypertensive spike. The research in this manuscript is not registered. This is a retrospective study.